The Clinical Application of Pulsed Radiofrequency Induces Inflammatory Pain via MAPKs Activation: A Novel Hint for Pulsed Radiofrequency Treatment - Feng-Yen Lin (MDPI AG, 2021)
Pulsed radiofrequency (PRF) works by delivering short bursts of radiofrequency to a target nerve, thereby affecting nerve signal transduction to reduce pain. Although preliminary clinical investigations have shown that PRF treatment can be used safely as an alternative interventional treatment in patients with refractory pain conditions, unexpected damage to a normal nerve/ganglion is still one of the possible complications of using the PRF strategy. Noxious pain may also be triggered if PRF treatment accidentally damages an intact nerve. However, few studies in the literature have described the intracellular modifications that occur in neuronal cells after PRF stimulation. Therefore, in this study, we evaluated the effects of PRF on unimpaired nerve function and investigated the potential mechanisms of PRF-induced pain. Wistar rats were stimulated with 30–60 V of PRF for 6 min, and mechanical allodynia, cold hypersensitivity, cytokine and matrix metalloproteinase (MMP) production, and mitogen-activated protein kinase activity (p38 MAPK, ERK1/2, JNK/SAPK) were analyzed. The results indicated that PRF stimulation induced a significant algesic effect and nociceptive response. In addition, the protein array and Western blotting analyses showed that the clinical application of 60 V of PRF can induce the activation of MAPKs and the production of inflammatory cytokines and MMPs in the lumbar dorsal horn, which is necessary for nerve inflammation, and it can be suppressed by MAPK antagonist treatment. These results indicate that PRF stimulation may induce inflammation of the intact nerve, which in turn causes inflammatory pain. This conclusion can also serve as a reminder for PRF treatment of refractory pain.